Estudio de la viabilidad técnica de un sistema de captación de energía piezoeléctrica con aplicación en plantillas de calzado deportivo - Norabuena Aliaga, Fiama Vanessa (2021)
The subject of this project is the study of the technical feasibility of developing a piezoelectric energy harvester system with application in sports shoe insoles. The objective is to propose a system for capturing the energy generated from the footsteps while walking, for the charging of low-power devices. The first chapter presents the problem that was detailed with the introduction, the problem statement, the general and specific objectives, the hypothesis to be validated at the end of the project, and the technical, inventive and environmental sustainability justifications. The second chapter deals with the theoretical framework of the research. Scientific articles and thesis were reviewed to elaborate the referential framework, and key concepts were defined as part of the conceptual framework and the glossary of terms. The third chapter exposes the engineering of the project. Existing technologies and the process of elaboration of the piezoelectric energy collection system are described. In the fourth chapter, the qualitative and quantitative results of the experimental tests of the prototypes, energy harvesting system and the reviewed literature are disclosed. In the fifth chapter, the research project finishes with the conclusions and recommendations.